Notula a Marziale su acrostici (e non solo) dai libri VIII e X - Ceccarani, Daniele (AL. Rivista di studi di Anthologia Latina, 2024)
Abstract The short paper shows some wordplays in two Martial’s epigrams from books 8 and 10. This is an opportunity to hint, through the route of the acrostic and other technopaegnia, at Martial’s relationship with the Virgilian model and with the epigrams attributed to Seneca of Anthologia Vossiana.